2014
DOI: 10.1039/c3dt52967c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and reactivity of Ni site models of [NiFeSe] hydrogenases

Abstract: A series of structural models of the Ni centre in [NiFeSe] hydrogenases has been developed which exhibits key structural features of the Ni site in the H2 cycling enzyme. Specifically, two complexes with a hydrogenase-analogous four-coordinate 'NiS3Se' primary coordination sphere and complexes with a 'NiS2Se2' and a 'NiS4' core are reported. The reactivity of the complexes towards oxygen and protons shows some relevance to the chemistry of [NiFeSe] hydrogenases. Exposure of a 'NiS3Se' complex to atmospheric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 59 publications
2
48
0
Order By: Relevance
“…The bond distances are as expected: the nickel selenolate distances of 2.295(8) Å in [Ni(‘S 2 Se 2 ’)] are longer than the nickel thiolate distances of 2.184(3) Å in [Ni(‘S 4 ’)],[ 17a ] as observed with other nickel thiolate/selenolate complexes. [ 18 ] The five-membered rings in [Ni(‘S 2 Se 2 ’)] constrain the Se-Ni-S angles negligibly to 89.3(4)° and the seven-membered ring of the xylenediyl group pushes the S1-Ni-S2 angle to 99.4(2)° . There is a small tetrahedral distortion from the square plane around the nickel center with an angle of 11.1±1° between the planes Se1-Ni-S1 and Se2-Ni-S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond distances are as expected: the nickel selenolate distances of 2.295(8) Å in [Ni(‘S 2 Se 2 ’)] are longer than the nickel thiolate distances of 2.184(3) Å in [Ni(‘S 4 ’)],[ 17a ] as observed with other nickel thiolate/selenolate complexes. [ 18 ] The five-membered rings in [Ni(‘S 2 Se 2 ’)] constrain the Se-Ni-S angles negligibly to 89.3(4)° and the seven-membered ring of the xylenediyl group pushes the S1-Ni-S2 angle to 99.4(2)° . There is a small tetrahedral distortion from the square plane around the nickel center with an angle of 11.1±1° between the planes Se1-Ni-S1 and Se2-Ni-S2.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported on a series of nickel complexes as structural models of the nickel center in the active sites of the [NiFeSe] hydrogenases. [ 18 ] Herein, we report a dinuclear [NiFeSe] hydrogenase active site model, which includes an iron carbonyl to replicate the core features of the enzyme active site. The synthesis, characterization, and activity of [NiFe(‘S 2 Se 2 ’)(CO) 3 ] is reported and it has been compared with the previously reported[ 15d ] thiolate analogue [NiFe(‘S 4 ’)(CO) 3 ] to determine the influence of the chalcogenate donor on the properties of the complex (Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant attention has been drawn to whether electrocatalysis in organic solvents is of homogeneous or heterogeneous nature. More specifically, several studies on similar dithiolene‐ or thiolate‐containing systems have shown that under reductive conditions a molecular catalyst may decompose to form a material which deposits on the surface of the electrode and is responsible for the catalytic performance . Several diagnostic criteria have been used to identify if a process is truly catalytic, most notably rinse tests in which the electrode, after a scan or a potential has been applied for a period of time, is transferred to a fresh solution containing only the acid.…”
Section: Discussionmentioning
confidence: 99%
“…However, low energy conversion wileyonlinelibrary.com overpotentials (−50 to −300 mV). [ 13,17,[31][32][33] In our previous studies, we found that the ionic copper complex, (Cu(bztpen)) 2+ (bztpen = N -benzyl-N , N′ , N′ -tris(2-pyridylmethyl)ethylenediamine), was a highly active molecular catalyst for the HER, [ 34 ] but it gradually deposited on the surface of glassy carbon electrode (GCE) during long-term bulk electrolysis at −0.90 V versus standard hydrogen electrode (SHE). With curiosity to know more about the material deposited from (Cu(bztpen)) 2+ , we made continuous detailed studies on this material.…”
Section: Introductionmentioning
confidence: 99%